CIRCUS ART IN MODERN REALITIES: FUNCTIONS, PROBLEMS, PROSPECTS - Romanenkova, Julia; Paliychuk, Anna; Sharykov, Denys; Bratus, Ivan; Kuzmenko, Halyna; Gunka, Anna (Revista Inclusiones, 2021)
The circus has always been one of the most controversial culture branches for terminologisation. Even today this is a field to deal with cliches, stereotypes, a platform for discussions about this activity type independence and its role in modern society. Unfortunately, the circus sphere has to fight for the right to be recognized as an independent culture segment, as an art form, although the fact this type of entertainment has been one of the most popular in society since ancient times remains incontestable. The scientists began to define the circus status as a phenomenon in the cultural sphere "table of ranks" transferring this discussion to the scientific field. The Soviet circus school as the most powerful in the world and after Soviet Union collapse each of the former Soviet republics actually again created its own circus school on the post-Soviet territory, based on the Soviet circus traditions. Politics became the reason of the most powerful cultural branch appeared under the threat of death. And in today’s realities the threat has become even more realistic. The Russian and Ukrainian circus appeared the most powerful after the USSR collapse, each of the school was the famous Soviet circus legal successor.